Prose poetry and critical involvements (Journal of the College of Basic Education, 2026)
The prose poem as seen by some scholars is not new to our Arabic poetry. this new form acquired its inodern leqitimacy as a result of abolition of the boundaries separating Literary genres, and the new text became an open text, and then the so called (gender stylisl) appeared, which studies the fusion of Literary genres within the framework of anew stuley. Hence, the prose poem takes from poetry its condensation and rhythm, and from prose some of its techniques such as continuity of writing, narration, coding and dialogue. Accordingly, Arabic poetry can achieve its existence only by breaking down the walls of poetic tradition, and modernity is only achieved through rebellion and protest, and this modernity is a new vision in its comprehensive, Whether it is scicitific or artistic modernity, it is a question about the possible and a protest against the prevailing by separating from the past and adding some symbols to benefit from the heritage and trying to resucitake through a vision that emnates from the poetic self and achieves a qualiatative development in the current scales.